Payback analysis of E85- and CNG-powered vehicles in Hungary - Jobbágy, Péter (Applied Studies in Agribusiness and Commerce, 2012)
As a result of my analysis it was found that when purchasing a new alternative fuel car only a CNG-powered vehicle could be a reasonable choice, the extra cost of which (depending on its scale) ensures a return within 2 – 7 years, i.e. over the real expected duration of use of the car. However, the spread of these cars is determined by the lack of CNG fuel stations in Hungary. The E85-powered so called FFVs could become a competitive alternative with lower ethanol prices or moderate government support (for example a registration fee allowance similar to that enjoyed with hybrid vehicles, or reduced taxes).